Gaussian phase transition and critical exponents in spin-1 bond-alternative Heisenberg chains. (22nd December 2016) - Heng Su, Yao; Min Chen, Ai; Xiang, Chunhuan; Wang, Honglei; Xia, Cai-Juan; Wang, Jun
Abstract: The quantum Gaussian phase transition is investigated for the infinite spin-1 bond-alternative Heisenberg model in one spatial dimension. By using a tensor network representation with an infinite matrix product state approach, the ground state energy, bipartite entanglement entropy, non-local string order, and fidelity per lattice site are calculated to characterize the phase transition. At the quantum phase transition point, the scaling behavior of various physical observables with respect to the finite truncation dimension are discussed for the ground state wavefunctions. In addition, the central charge is extracted from the finite entanglement entropies and the finite correlation lengths. Furthermore, the various critical exponents of the string order are calculated. The characteristic critical exponents and the central charge determine the universality class of the phase transition.